Perovskite CH3NH3PbI3–XClx Solar Cells and their Degradation (Part 1: A Short Review) - Kaulachs, I.; Ivanova, A.; Tokmakov, Andrei; Roze, M.; Mihailovs, Igors; Rutkis, Martins (De Gruyter, 2021)
Development of hybrid organic-inorganic perovskite solar cells (PSC) has been one of the hottest research topics since 2013. Within brief literature review, we would like to achieve two objectives. Firstly, we would like to indicate that a whole set of physical properties, such as high change carrier mobility, very low recombination rates, large carrier life time and diffu-sion length, large absorption coefficients and very weak exciton binding energies, are defining high power conversion efficiency (PCE) of methyl ammonium lead trihalide SC. The second objective is to draw attention to some, in our opinion, important aspects that previously have not been satisfactory addressed in literature. Although degradation of PSC is widely discussed, processes at very first exposure to ambient conditions after deposition of top electrode are uncovered.---//---This work is licensed under a CC BY 4.0 license.
Keywords: Research Subject Categories::NATURAL SCIENCES:Physics; Inverted solar cells; lead halide perovskite; power conversion efficiency